2010
DOI: 10.1080/00015458.2010.11680592
|View full text |Cite
|
Sign up to set email alerts
|

Role of Angio-Embolisation in Trauma-Review

Abstract: AE is very useful in managing patients with isolated spleen and liver injuries non-operatively. It can be used alone or as an adjunct to damage-control surgery in complex polytraumas and may decrease the blood loss in pelvic injuries. Whenever a trauma patient with splenic injury is treated non-operatively, subsequent splenic artery pseudoaneurysm should not be forgotten and the patient should be followed up with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Very few studies were identified evaluating the clinical effectiveness of RBC or blood component therapy. Only two studies were identified which evaluated surgical or mechanical interventions, which is surprising given the interest in damage control surgery [72] and angio-embolization [73]. Tranexamic acid was the only pharmaceutical agent that improved mortality [56].…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies were identified evaluating the clinical effectiveness of RBC or blood component therapy. Only two studies were identified which evaluated surgical or mechanical interventions, which is surprising given the interest in damage control surgery [72] and angio-embolization [73]. Tranexamic acid was the only pharmaceutical agent that improved mortality [56].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients diagnosed with a pseudoaneurysm required more invasive intervention. Endovascular treatment currently remains first‐line therapy, particularly for abdominal/pelvic pseudoaneurysms 13,19 . However, Cordova et al 6 argued that endovascular techniques should be (in most cases) reserved electively and for poor surgical candidates due to the higher morbidity and mortality associated with endovascular technique in the emergent setting.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced or novel therapeutic methods applied either simultaneously or in a priority oriented way with the multidisciplinary cooperation of different specialists, have also contributed in the improved quality of the provided polytrauma care. In addition to standard life saving surgery such as laparotomy, thoracotomy or application of a pelvic C-clamp and concomitant pelvic packing (Probst et al, 2009), advances made in interventional radiology have improved the management of patients with solid organ trauma or pelvic ring injuries by angio-embolisation without the need for immediate surgical intervention or as adjunct to damage-control surgery in complex injury patterns (Shaftan, 2008; Durai and Ng, 2010). However, such interventions are not without risks and, although less invasive, patients should be followed up carefully (Durai and Ng, 2010).…”
Section: Introductionmentioning
confidence: 99%